Impact of HIV Pretreatment Drug Resistance on Secondary Transmission Through Treatment Dropout: A Prospective Population-Based Study in Southwestern China - Chen Y; Xu X; Chen H; Zhang X; Zhu Q; Liang S; Xing H; Liao L; Feng Y; Shao Y; Ruan Y; Lan G; et al. (Infection and Drug Resistance)
Yi Chen,1,* Xiaoshan Xu,2,* Huanhuan Chen,3,* Xiangjun Zhang,4 Qiuying Zhu,3 Shujia Liang,3 Hui Xing,2 Lingjie Liao,2 Yi Feng,2 Yiming Shao,2 Yuhua Ruan,2 Guanghua Lan,3 Jianjun Li3 1The Guangxi Academy of Medical Sciences, The People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, People’s Republic of China; 2State Key Laboratory of Infectious Disease Prevention and Control (SKLID), Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, National Center for AIDS/STD Control and Prevention (NCAIDS), Chinese Center for Disease Control and Prevention (China CDC), Beijing, People’s Republic of China; 3Guangxi Key Laboratory of Major Infectious Disease Prevention Control and Biosafety Emergency Response, Guangxi Center for Disease Control and Prevention, Nanning, People’s Republic of China; 4Center for Community Research and Evaluation, University of Memphis, Memphis, TN, USA*These authors contributed equally to this workCorrespondence: Yuhua Ruan, Email ruanyuhua92@chinaaids.cn Jianjun Li, Email lijianjun810@sina.comObjective: Discontinuation of antiretroviral treatment (ART) raised drug resistance and failure of Human Immunodeficiency Virus (HIV) virological suppression. The study aimed to assess the relationship between pretreatment drug resistance (PDR) and ART dropout, as well as the relationship between HIV treatment dropout and HIV secondary transmission.Methods: This study included all eligible participants from a local surveillance database in southwestern China between 2014 and 2021. The PDR prevalence trend was assessed using trend Chi-square tests within a consecutive cross-sectional design (N = 3060). Cox proportional hazards model was used to investigate the relationship between PDR and the risk of treatment dropout within a cohort design. Generalized Estimating Equations model was applied to explore the association between treatment dropout and HIV secondary transmission within a longitudinal genetic network study design. (N = 5094).Results: The overall PDR prevalence was 6.2%, analyzing a study sample of 3060 individuals with HIV/AIDS. Specifically, the prevalence of PDR to non-nucleoside reverse transcriptase inhibitors (NNRTIs), nucleoside reverse transcriptase inhibitors (NRTIs), and protease inhibitors (PIs) was 3.6%, 1.4%, and 1.1%, respectively. Yearly difference in prevalence was not identified. The independent association between PDR to NNRTIs and treatment dropout was significant (adjusted hazard ratio: 2.55, 95% CI 1.52– 4.29). Among 5094 newly diagnosed HIV cases, participants who dropped out did not show a significant difference in HIV secondary transmission compared to those not on ART (adjusted odds ratio: 1.15, 95% CI 0.74– 1.79).Conclusion: PDR to NNRTIs may contribute to HIV secondary transmission through treatment dropout. It is imperative to offer comprehensive and advanced HIV care for all individuals with HIV, enhance treatment and medication adherence, and closely monitor PDR prevalence.Keywords: HIV, pre-treatment drug resistance, treatment dropout, HIV secondary transmission